Transcriptome analysis of gonads and brain of giant freshwater prawn (Macrobrachium rosenbergii): screening and validation of genes related to germ cell development - Wei, Jie; Hong, Kunhao; Zhou, Qiaoyan; Wang, Yakun; Li, Wei; Liu, Xiaoli; Hong, Xiaoyou; Chen, Chen; Yu, Lingyun; Zhu, Xinping (Frontiers in Marine Science, 2022)
Precocious puberty in Macrobrachium rosenbergii, an important farmed shrimp worldwide, leads to severe economic losses. Although reproductive sterilization can avoid this problem, little is known about the molecular mechanisms underlying gonadal development and gametogenesis in M. rosenbergii. Here, we conducted transcriptome analysis of the ovaries, testes, and male/female brain tissues of M. rosenbergii to discover germ cell development-related genes. A total of 60,607 unigenes were identified, of which 20,963 unigenes could be functionally annotated. Venn diagram analysis, keywords and known markers searching, followed by the elimination of low expression and repetitive genes, identified 18 candidate genes. Subsequent real-time quantitative reverse transcription polymerase chain reaction and in situ hybridization identified five genes (RAD51, vasa, SPDS, MRR, and Fem-1C) associated with germ cell development—RAD51, vasa, and SPDS were expressed in both male and female gonads, whereas Fem-1C was specifically expressed in the ovaries and MRR in the testis. In the ovary, vasa, SPDS, and Fem-1C were mainly expressed in stage 1–3 oocytes, while RAD51 was expressed in stage 2–3 oocytes. In testis, vasa was significantly expressed in spermatogonia and primary spermatocytes, whereas RAD51 and SPDS were only enriched in spermatogonia and MRR in vas deferens. Our research indicates that these five genes are important germ cell development-related genes, of which RAD51, SPDS, and Fem-1C were proven to function in germ cells of this species for the first time. The discovery of these genes could help develop molecular breeding techniques to overcome precocious puberty in M. rosenbergii.